Activation of enzymatically produced chitooligosaccharides by dioxyamines and dihydrazides. (15th March 2020) - Vikøren Mo, Ingrid; Feng, Yiming; Øksnes Dalheim, Marianne; Solberg, Amalie; Aachmann, Finn L.; Schatz, Christophe; Christensen, Bjørn E.
Graphical abstract: Highlights: Chitooligosaccharides of the type Dn XA were obtained enzymatically. Activation with a dioxyamine or a dihydrazide was studied in detail. Major differences in kinetics, yields and distribution of reaction products. One-pot reductive amination protocols with α-picoline borane were developed. Comparison to dextran demonstrated major differences in conjugation kinetics. Abstract: Reducing end activation of poly- and oligosaccharides by bifunctional dioxyamines and dihydrazides enables aniline-free and cyanoborohydride-free conjugation to aldehyde-containing molecules, particles and surfaces without compromising the chain structure. Chitosans are due to their polycationic character, biodegradability, and bioactivity important candidates for conjugation. Here, we present a kinetic and structural study of the conjugation of a dioxyamine and a dihydrazide to enzymatically produced chitooligosaccharides ranging from N, N '-diacetylchitobiose to a decamer, all having N -acetyl d -glucosamine at the reducing end. Conjugation of the dioxyamine resulted in mixtures of ( E )- and ( Z )-oximes and β- N -pyranoside, whereas the dihydrazide yielded cyclic N -glycosides. Reaction kinetics was essentially independent of DP. Stable secondary amines were in both cases obtained by reduction with α-picoline borane, but higher temperatures were needed to obtain acceptable reduction rate. Comparison to dextran oligomers shows that the nature of the reducing end strongly influences the kinetics of both the conjugation and reduction.